Prosocial behaviors of junior high school students of the vicariate of Saint Francis of the Diocese of San Fernando, La Union - Dumaguin, Romeo D. (Saint Louis College, City of San Fernando, La Union : [s.n.], 2017)
The descriptive study assessed the manifestation of prosocial behaviors among the Junior High School students of the Vicariate of Saint Francis of the Diocese of San Fernando, La Union as basis in crafting a development plan. Specifically, it assessed the profile of participants in terms of sex and grade level, level of manifestation of prosocial behaviors along altruistic, complaint, emotional, dire, public, and anonymous behavior; correlations among the manifestation of the prosocial beharviors and differences of the manifestation of prosocial behaviors when grouped according to the profile variables individually and interaction with each other.
Bibliography: pages 105-110.
CHED-La Union
Keywords: Students